2002
DOI: 10.1016/s0893-133x(02)00330-5
|View full text |Cite
|
Sign up to set email alerts
|

Aging and Panicogenic Response to Cholecystokinin Tetrapeptide An Examination of the Cholecystokinin System

Abstract: Older age is associated with diminished symptomatic and cardiovascular response to the panicogenic agent cholecystokinin tetrapeptide (CCK-4). We hypothesized that circulating concentrations of endogenous CCK-4 and/or CCK-8 are increased in later life, possibly due to decreased enzymatic degradation, and that this is associated with desensitization of CCK-B receptors. The study group consisted of 20 healthy subjects aged 18-30 years and 20 healthy subjects aged years. The two groups were compared on fasting ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…This CCK-induced hypercholesterolemia might be clinically important. It has been reported that bile release [30] as well as the plasma cholesterol and CCK levels [31] increase with age. It is highly possible that the age-related increase in plasma CCK is responsible for the increased bile release and hypercholesterolemia.…”
Section: Discussionmentioning
confidence: 99%
“…This CCK-induced hypercholesterolemia might be clinically important. It has been reported that bile release [30] as well as the plasma cholesterol and CCK levels [31] increase with age. It is highly possible that the age-related increase in plasma CCK is responsible for the increased bile release and hypercholesterolemia.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that the incidence and prevalence of PD decline in later life (48). The reason for this decline is unknown, but it has been hypothesized that circulating concentrations of endogenous CCK4 and/or CCK8 are increased in later life, possibly due to decreased enzymatic degradation and that this is associated with desensitization of CCK-2 receptors (49).…”
Section: Human Studiesmentioning
confidence: 99%
“…Time and experience are thought to aid in the development of emotional regulation (Jarvik & Russell, ). Moreover, age‐related atrophy of the locus coeruleus and other anxiety‐associated brain regions, as well as changes in peripheral physiology, are thought to attenuate anxious arousal in older individuals (Flint, ; Flint et al, ). However, aging is associated with degeneration of other brain regions that promote adaption to anxiety, for instance, the dorso‐lateral prefrontal cortex.…”
Section: Introductionmentioning
confidence: 99%